PENGARUH PENGETAHUAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH (SAK EMKM), COMPUTER SELF-EFFICACY, DAN FACILITATING CONDITIONS TERHADAP MINAT MENGGUNAKAN APLIKASI AKUNTANSI - Fazrin Defillateli; Bambang Sugiharto; Indah Umiyati (Universitas Pamulang, 2020)
Small and Medium-Sized Enterprises in Indonesia will continue to grow from year to year, which will support Indonesia's economy. The aim of this research was to find out and analyze the influence of knowledge effects of Financial Accounting Standards of Small and Medium-Sized Enterprises (SMEs), Computer Self-efficacy, and Facilitating Conditions to the intention to using accounting applications Small and Medium-Sized Enterprises (SMEs). The study used three independent variables that are the knowledge of Financial Accounting Standards of Small and Medium-Sized Enterprises (SMEs), Computer Self-efficacy, and Facilitating Conditions, while intention to using accounting applications as a dependent variable. The sample of this research were Small and Medium-Sized Enterprises (SMEs) in Subang Regency, West Java Province. Sampling Incidental of non-probability sampling was used as a sampling method with the total sample of 205 people. Validity, reliability, descriptive analysis, classical assumption test, and multiple regression analysis is used for this study. The results of this research indicate that knowledge of Financial Accounting Standards of Small and Medium-Sized Enterprises (SMEs), Computer Self-efficacy, and Facilitating Conditions have a positive effect to the intention in using either accounting application, the results of tests on each variable or simultaneously. Keyword: Knowledge of Financial Accounting Standards of Small and Medium-Sized Enterprises (SMEs); Computer Self-efficacy; Facilitating Conditions; Intention To Use; Accounting Application